اردو تنقید میں نونظری رجحانات اور مابعد جدیدیت: فکری ڈھانچے اور امتیازات: Urdu Tanqeed Mein Nau Nazari Rujhanat Aur Ma Baad Jadidiyat: Fikri Dhanchay Aur Imtiyazat - Hussain, Zahid; Akbar, Dr. Sumera (Zoraiz, 2025)
In Urdu literary criticism, neo-trends are often associated with modernism and postmodernism. However, neo-trends and postmodernist theories represent two distinct intellectual frameworks that have profoundly influenced contemporary thought. Both challenge traditional narratives, yet they differ significantly in their perspectives, fundamental philosophies, and impact on contemporary discourse. This study aims to analyze the key aspects of neo-trends and postmodernist theories, highlighting their conceptual differences and examining their role in shaping literary and critical thought. By exploring their theoretical foundations, this paper seeks to clarify the nuanced relationship between these two movements and their relevance in Urdu criticism.